2021
DOI: 10.1186/s12885-021-08360-z
|View full text |Cite
|
Sign up to set email alerts
|

A glycolysis-based three-gene signature predicts survival in patients with lung squamous cell carcinoma

Abstract: Background Lung cancer is one of the most lethal and most prevalent malignant tumors worldwide, and lung squamous cell carcinoma (LUSC) is one of the major histological subtypes. Although numerous biomarkers have been found to be associated with prognosis in LUSC, the prediction effect of a single gene biomarker is insufficient, especially for glycolysis-related genes. Therefore, we aimed to develop a novel glycolysis-related gene signature to predict survival in patients with LUSC. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Furthermore, we compared the performance of the present signature with those of the other previously reported gene signatures in LUSC. The RMS curve showed that the performance of the present signature was similar to that of the other four signatures ( Supplementary Figure S3C ) ( Huang et al, 2021 ; Li et al, 2021 ; Li et al, 2022 ; Zhai et al, 2022 ). These results suggest that the CSRG signature can serve as a candidate prognostic biomarker for survival in patients with stage I–III LUSC.…”
Section: Resultssupporting
confidence: 57%
“…Furthermore, we compared the performance of the present signature with those of the other previously reported gene signatures in LUSC. The RMS curve showed that the performance of the present signature was similar to that of the other four signatures ( Supplementary Figure S3C ) ( Huang et al, 2021 ; Li et al, 2021 ; Li et al, 2022 ; Zhai et al, 2022 ). These results suggest that the CSRG signature can serve as a candidate prognostic biomarker for survival in patients with stage I–III LUSC.…”
Section: Resultssupporting
confidence: 57%
“…Human malignancies, including LUSC, are often characterized by aerobic glycolysis, also known as the Warburg effect ( Cao et al, 2020 ). However, studies on the Warburg effect often focus on hepatocellular carcinoma or breast cancer ( Li et al, 2018 ; Zheng et al, 2019 ; Huang et al, 2021 ; Zuo et al, 2021 ). Few studies on the Warburg effect in LUSC have been reported ( Wang et al, 2018 ; Hoang et al, 2019 ; Cao et al, 2020 ; Woźniak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, only MDH1 expression was associated with poor prognosis in patients diagnosed with NSCLC 15 , 16 . MDH1 is predicted to be a prognostic marker of lung squamous cell carcinoma (LUSC) based on multivariate Cox regression analysis 17 . In addition, the frequency of MDH1 mutations in LUSC is 5% in the cBioPortal database 17 .…”
Section: Discussionmentioning
confidence: 99%
“…MDH1 is predicted to be a prognostic marker of lung squamous cell carcinoma (LUSC) based on multivariate Cox regression analysis 17 . In addition, the frequency of MDH1 mutations in LUSC is 5% in the cBioPortal database 17 . SLC8A1 downstream intergenic region ALK fusion was detected in patients with advanced lung adenocarcinoma 18 .…”
Section: Discussionmentioning
confidence: 99%